2018
DOI: 10.1007/s42452-018-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a new method for synthesizing amine functionalized g-C3N4 nanosheets for application as anti-corrosion nanofiller in epoxy coatings

Abstract: In this research, the effect of graphitic carbon nitride (g-C 3 N 4) on the corrosion protection performance of solvent-based epoxy coatings is investigated. The g-C 3 N 4 is synthesized by two-step condensation of melamine and is characterized by X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, and carbon-hydrogennitrogen elemental analysis. In order to enhance the dispersion of g-C 3 N 4 in epoxy coating, it is chemically functionalized with ethylenediamine vapor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Other materials used to enhance the dispersion of g-C 3 N 4 in waterborne coatings or to enhance its mechanical properties as a filler include polyaniline formed on the surface of g-C 3 N 4 [203], molybdenum oxides, MoO x [205], and SiO 2 with TiO 2 [206]. Also, g-C 3 N 4 has been functionalized with ethylenediamine vapor to enhance its dispersion in a solvent-based epoxy [207]. Clearly, the 2D g-C 3 N 4 nanosheets can be hybridized with other components to design more corrosion-protective coatings.…”
Section: Graphitic Carbon Nitridementioning
confidence: 99%
“…Other materials used to enhance the dispersion of g-C 3 N 4 in waterborne coatings or to enhance its mechanical properties as a filler include polyaniline formed on the surface of g-C 3 N 4 [203], molybdenum oxides, MoO x [205], and SiO 2 with TiO 2 [206]. Also, g-C 3 N 4 has been functionalized with ethylenediamine vapor to enhance its dispersion in a solvent-based epoxy [207]. Clearly, the 2D g-C 3 N 4 nanosheets can be hybridized with other components to design more corrosion-protective coatings.…”
Section: Graphitic Carbon Nitridementioning
confidence: 99%
“…The dispersion of nanomaterials plays a decisive role in improving the anticorrosive ability of coatings; therefore, improving g -C 3 N 4 dispersion in coatings is an important challenge. Pourhashem et al reported that after functionalization of g -C 3 N 4 by ethylenediamine using a chemical method, there is significant improvement in g -C 3 N 4 dispersion and the anticorrosive properties of epoxy (EP) coatings. However, the preparation process is relatively cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater acts as a powerful corrosive medium; hence mild steel will certainly face significant corrosion in the harsh marine environment. Because of the presence of chloride ions or other aggressive species in seawater, the passivity of the steel may be affected by the breakdown of the passive layer. It produces corrosion on the metal surfaces of the infrastructure, which results in a number of problems, including safety risks and significant financial losses due to the time and money needed to repair and replace the equipment. , Corrosion protection technology for mild steel in a marine environment has thus emerged as a popular study area. The researchers are dedicated to pursuing a variety of practical and cost-effective solutions, such as the inclusion of corrosion inhibitors, the application of polymeric coatings that resist corrosion, or electrochemical protection, to increase the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…It produces corrosion on the metal surfaces of the infrastructure, which results in a number of problems, including safety risks and significant financial losses due to the time and money needed to repair and replace the equipment. 9,10 Corrosion protection technology for mild steel in a marine environment has thus emerged as a popular study area. The researchers are dedicated to pursuing a variety of practical and cost-effective solutions, such as the inclusion of corrosion inhibitors, the application of polymeric coatings that resist corrosion, or electrochemical protection, to increase the lifespan.…”
Section: Introductionmentioning
confidence: 99%